Numerical solution of linear Volterra integral equations system of the second kind - Tahmasbi, Ali; Fard, Omid S. (Applied mathematics and computation, 2008)
There are several numerical approaches for solving linear Volterra integral equations system of the second kind. In this paper, we have presented a method for numerical solution of linear Volterra integral equations system based on the power series method, the major advantage of which is being derivative-free. Also, this method reproduces the analytical solution when the exact solutions are polynomial. The numerical results prove that the presented method is very effective and simple. The software used for the numerical calculations in this study was MATLAB ®7.4.